Integrated analysis reveals the protective mechanism and therapeutic potential of hyperbaric oxygen against pulmonary fibrosis - Yuan Yuan; Guoqiang Qiao; Jiajiao Zhou; Yilu Zhou; Yali Li; Xia Li; Zhenglin Jiang; Yihua Wang (Genes and Diseases, 2023)
Idiopathic pulmonary fibrosis (IPF) is a dreadful, chronic, and irreversibly progressive disease leading to death with a few effective treatments. Our previous study suggested that repetitive hyperbaric oxygen (HBO) treatment alleviates bleomycin-induced pulmonary fibrosis in mice. Here, we investigated the protective mechanism of HBO treatment against pulmonary fibrosis using an integrated approach. Analyzing publicly available expression data from the mouse model of bleomycin-induced pulmonary fibrosis as well as IPF patients, several potential mechanisms of relevance to IPF pathology were identified, including increased epithelial-to-mesenchymal transition (EMT) and glycolysis. High EMT or glycolysis scores in bronchoalveolar lavage were strong independent predictors of mortality in multivariate analysis. These processes were potentially driven by hypoxia and blocked by HBO treatment. Together, these data support HBO treatment as a viable strategy against pulmonary fibrosis.